The Challenge to Mahmoud Abu Rayyah's Thoughts on The Significance of Abu Hurairah and Ka'b Al-Ahbār in Hadīth Narration - Jamal Ahmed Bashier Badi; Saadeldin Mansour Gasmelsid; Alhafidh Nasution (Universiti Sains Islam Malaysia, 2024)
Journal Of Hadith Studies, Volume 9 Issue 2 Page (1-10)